2005
DOI: 10.3844/ajessp.2005.102.105
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Mercury from chlor-alkali Industry Wastewater using Acetobacter xylinum Cellulose

Abstract: Abstract:In this study, the removal of mercury ions by cellulose of Acetobacter xylinum was investigated in the synthetic and chlor-alkali wastewater. Biofilms of Acetobacter xylinum were grown in laboratory column bioreactors. The biofilms were continuously treated with sterile synthetic model wastewater or nonsterile, neutralized chloralkali wastewater.The extent of adsorption was studied as function of pH, adsorbent dose and contact time. Efficiency of mercury ion removal from chlor-alkali industry wastewat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 16 publications
(11 reference statements)
1
18
0
2
Order By: Relevance
“…The major effects of mercury poisoning manifest as neurological and renal disturbances as it can easily pass the blood-brain barrier and has effect on the brain [26].…”
Section: Mercury (Hg)mentioning
confidence: 99%
See 1 more Smart Citation
“…The major effects of mercury poisoning manifest as neurological and renal disturbances as it can easily pass the blood-brain barrier and has effect on the brain [26].…”
Section: Mercury (Hg)mentioning
confidence: 99%
“…Environmental contamination due to mercury is caused by several industries, petrochemicals, minings, painting, and also by agricultural sources such as fertilizer and fungicidal sprays [26]. Some of the more common sources of mercury found throughout the environment include but may not be limited to the household bleach, acid, and caustic chemicals (e.g., battery acid, household lye, muriatic acid (hydrochloric acid), sodium hydroxide, and sulfuric acid), instrumentation containing mercury (e.g., medical instruments, thermometers, barometers, and manometers), dental amalgam (fillings), latex paint (manufactured prior to 1990), batteries, electric lighting (fluorescent lamps, incandescent wire filaments, mercury vapor lamps, ultraviolet lamps), pesticides, pharmaceuticals (e.g., nasal sprays, cosmetics, contact lens products), household detergents and cleaners, laboratory chemicals, inks and paper coatings, lubrication oils, wiring devices and switches, and textiles.…”
Section: Mercury (Hg)mentioning
confidence: 99%
“…Among the various matrixes that are available, the MC has been chosen for its ease of use, low economic cost, low toxicity, and high operational stability (Rezaee et al, 2005;Son et al, 2003). The MC synthesized by Acetobacter xylinum is identical to that made by plants in respect to molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…The possible noticeable effects of mercury in birds are decreased egg weight, fertility, and hatchability. Increase in kidney lesions, brain lesions, skeletal deformities; reduced clutch size, poor hatchability, poor embryonic growth, behavioural change and neurologic signs of weakness and inadequate coordination in wild birds [57]. It has also been demonstrated that the occurrence of deformities increases rapidly when selenium concentrations in fish eggs are greater than 10mg/kg [58].…”
Section: Effects Of Heavy Metals On Bird Speciesmentioning
confidence: 99%